Changes in Candida Profile in Patients Undergoing Intensity Modulated Radiotherapy for Head and Neck Malignancies - Kamath, Jasmine Shanthi; Kini, Raghavendra; Naik, Vathsala; Shetty, Anup Kumar (UI Scholars Hub, 2017)
The increased oral Candida colonization that resulted for radiotherapy often leads to candidiasis. Intensity Modulated Radiotherapy (IMRT) is a technique of delivering radiation with improved dose distributions sparing the surrounding normal tissue and decreasing the ill-effects. Objective: To identify and quantify changes in the Candidal carriage of patients undergoing IMRT for head and neck malignancy. Methods: Saliva from 37 patients undergoing IMRT for head and neck malignancy was collected. The Candida species profile pre- and post-IMRT was evaluated using semi quantitative fungal culture. The changes in the distribution of the growth of Candida species due to IMRT was analyzed using Wilcoxon sign rank test. Results: Twenty-two patients were Candida-positive pre-IMRT, while 24 patients were Candida-positive post-IMRT. Candida species isolates pre-IMRT were C. albicans (63%), C. tropicalis (26%), C. glabrata (7%), C. krusei (4%) and post-IMRT, were C. albicans (55%), C. tropicalis (30%), C. glabrata (12%) and C. krusei (3%). C. albicans showed increased growth post-IMRT in the range of 103 to 104 colony-forming units per ml of saliva (p>0.05). Conclusion: There was no significant effect of IMRT on the distribution of growth of Candida. Candida albicans was the most common species. A change towards non C. albicans species post-IMRT was seen.